片側性そしゃく筋の重度形成不全を伴った顔面非対称の１例 - SAKAMOTO Ichiro; YODA Tetsuya; NARITA Noriyuki; IMAI Hideki; ISHIKAWA Motoi; TSUSHIMA Fumihiko; SAKURAI Jinkyo; TSUKAHARA Hiroyasu; MIYAMURA Juichi; YODA Yasushi; OMURA Ken (Journal of the Japanese Society for the Temporomandibular Joint, 2004)
A case of facial asymmetry with severe unilateral hypoplasia of the masticatory muscles is reported. A 45-year-old Japanese man was referred to our clinic on Dec. 18, 2002 with chief complaint of dull pain of the right masseter and molar teeth during chewing. He presented with left side facial hypoplasia which had been noted from an early age. The external ear was normal, the ears symmetrically placed and audition showed no abnormality. Maximal mouth opening was 58mm and the mandible did not deviate upon opening the mouth. Radiographic examination did not reveal any dental abnormalities but the left ramus and condyle of the mandible was found to be smaller than the right and to have a less well developed gonial angle. MR imagings of facial tissues showed that the masseter, temporalis and medial pterygoid muscles were grossly hypoplastic and the lateral pterigoid mildly so on the left side. The clinical findings thus suggested that this was not a typical case of a first and second branchial arch syndrome. 今回われわれは, 片側性咀嚼筋の重度形成不全を伴った顔面非対称の1例を経験したので報告する。患者は, 45歳男性で, 食事時の右側臼歯部と咬筋部の鈍痛を主訴に, 2002年12月に当科を受診した。患者は, 幼少時より右側咬筋部が左側に比べて張り出していることを自覚していた。両側外耳形態と聴力に異常は認めなかった。最大開口域は58mmで, 開口時に下顎の偏位を認めなかった。X線検査では, 明らかな歯科的異常は認められず, 左側の下顎枝・下顎角・下顎頭は右側に比べて矮小であった。MRIでは左側の咬筋・側頭筋・内側翼突筋の重度な形成不全を認め, 左側の外側翼突筋も矮小であった。臨床所見から, 本症例は第一・第二鯉弓症候群の亜型の一つである可能性が考えられた。